THE STRUGGLE FOR RECOGNITION AND THE POLITICS OF IDENTITY: A FEMINIST JURISPRUDENTIAL APPROACH TO PRESIDENT OF THE REPUBLIC OF SOUTH AFRICA V HUGO (The Pretoria Student Law Review, 2021)
Equity feminism characterised by an almost egalitarian idealism, raises an irreconcilable paradox: is it possible to be egalitarian or profess to be fighting for equality when presenting a view of the world solely from a woman’s perspective; impoverished from the very thing it desires? It is this ideological framework under which this paper seeks to redress the majority judgment made in President of the Republic of South Africa v Hugo.
Keywords: Equity feminism; egalitarian idealism; President of the Republic of South Africa v Hugo; irreconcilable paradox; equality